2010
DOI: 10.1128/jcm.02427-09
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Genotype Analysis of Emerging Sapovirus-Associated Infections across Europe

Abstract: Sapoviruses (SaVs) belong to the Caliciviridae family and can cause gastroenteritis in humans and swine. Despite extensive testing, human sapoviruses have been found only in sporadic cases and in one mixed outbreak in children between 1994 and 2007 in the Netherlands. Here we describe a change in sapovirus epidemiology in the Netherlands resulting in sapovirus outbreaks and infections in adults. From November 2007 to January 2009, 478 outbreaks of acute gastroenteritis were reported to the National Institute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
103
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 34 publications
14
103
1
1
Order By: Relevance
“…Genogroup IV has been frequently reported in children as well as adults with gastroenteritis [4,10,32,33] and particularly in SaV-associated outbreaks [7,8,34,35]. The second most prevalent and widely-distributed genotype, GI.2, is also frequently reported in patients with gastroenteritis worldwide [6,8,10,30,31]. Strains from SA shared even higher nucleotide identity (99-100%) with SaVs from other countries, particularly recent strains reported in Asia (2012) [18] and Japan (2003) [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genogroup IV has been frequently reported in children as well as adults with gastroenteritis [4,10,32,33] and particularly in SaV-associated outbreaks [7,8,34,35]. The second most prevalent and widely-distributed genotype, GI.2, is also frequently reported in patients with gastroenteritis worldwide [6,8,10,30,31]. Strains from SA shared even higher nucleotide identity (99-100%) with SaVs from other countries, particularly recent strains reported in Asia (2012) [18] and Japan (2003) [5].…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests stability of the genotype as older strains from 2003 shared high nucleotide identities over the partial capsid gene region to strains as recent as 2012 and 2013. Genogroup IV has been frequently reported in children as well as adults with gastroenteritis [4,10,32,33] and particularly in SaV-associated outbreaks [7,8,34,35]. The second most prevalent and widely-distributed genotype, GI.2, is also frequently reported in patients with gastroenteritis worldwide [6,8,10,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in Belém showed that SaV was detected in 4.9% (15/ SaV GI.1 is known to be the predominant genotype worldwide. In Europe, this genotype was identified as the cause of 11 outbreaks of gastroenteritis; in most of them, the patients were adults older than 60 years 33 . In addition, genotype GII.1 presents a high prevalence compared to other SaV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…SaVs are often associated with sporadic, selflimiting gastroenteritis, the severity of which is reportedly milder than that of NoVs (5,6). However, SaVs also cause outbreaks worldwide (7)(8)(9)(10), and deaths associated with SaV infection have been reported for long-term-care facilities (11).…”
mentioning
confidence: 99%